IMPLEMENTASI PEMBELAJARAN DARING PADA MATA PELAJARAN BAHASA INDONESIA DI SMAN 13 MAKASSAR - Arifa Lestari; Ramly Ramly (Fakultas Teknik Universitas Negeri Makassar, 2022)
Implementation of the Online Learning Model in Indonesian Language Subjects at SMAN 13. This study aims to describe and describe the implementation of online learning in Indonesian language subjects at SMAN 13 Makassar. This research is a descriptive qualitative type with data in the form of online learning implementations sourced from the online learning process in three classes and three teachers using observation, interview, and documentation data collection techniques which are then analyzed starting from data transcripts, data reduction, analyzing and presenting data, and draw a conclusion. This study obtained the results that: SMAN 13 Makassar actually implements online learning. The implementation of learning is assisted by the WhatsApp application as the main application assisted by Google Classroom, and Zoom Meeting In the concept implementation process, the Teacher Center is applied and students become passive figures in the learning process. The evaluation process runs almost the same as the offline process. The difference is that the shape of the object being evaluated is converted into a photo, video, or softfile.